Retreating From Life: The Boy Whose Body Experienced His Pain. (December 2018) - Harwood, Anna; Shalev, Amit; Ben-Shaul, Sharon; Meir, Rachel; Kiansky, Ela; Horn, Keren; Deitcher, Chane; Dror, Sima; Galili, Esti
The expression of psychological distress through somatic symptoms is most prevalent among children. Somatic symptom disorders represent a difficult category of disorders to treat and they are often misdiagnosed due to their physical symptomology and dismissed due to their malingering stigma. The current case report follows the treatment of David, a 10-year-old Caucasian male, admitted into the pediatric psychiatric ward of a general hospital, uncommunicative, showing little signs of responsiveness, and dependent on nursing staff for basic needs. Following a complex treatment protocol which integrated key elements of psychodynamic and cognitive-behavior (CBT) treatment recommendations for somatic disorders, David was discharged after 6 months as an inpatient. This in-depth case study provides a synthesis of the varied research on somatic symptom disorders and an acute understanding of how to combine the understanding of complex family dynamics and individual personality structure with empirically reinforced treatment strategies.